Penerapan Layanan Konseling Kelompok Sebagai Upaya Mengatasi Keterlambatan Siswa Kelas IX I Semester 1 SMP Negeri 8 Denpasar Tahun Pelajaran 2023/2024 - Siti Nurhayati; Baiq Isna Maulida Famuji; Irfan Ramdhoni; Putu Agus Semara Putra Giri (Politeknik Kampar, 2024)
Education in schools is planned education which in its implementation involves various components. The presence of students at school to take part in learning activities is one of the factors in student learning success. The main objective of this research is to: Overcome late students in class IX I Semester I of SMP Negeri 8 Denpasar for the 2023/2024 academic year by implementing group counseling services. The data collected in this research is data regarding student learning outcomes using counseling service guidance. The tools used in this method are the Laiseg, Laijapen, Laijapan tools which consist of counseling services, group counseling created by researchers adapted to the subject matter in the syllabus which is implemented at the end of each cycle. Judging from the frequency of scores obtained from research subjects based on data analysis, it can be concluded that the implementation of group counseling services can overcome delays in class IX I Semester I students at SMP Negeri 8 Denpasar for the 2022/2023 academic year. This is evident from the results of the data which experienced an increase in each cycle, namely initially 32%, cycle I 59% and in cycle II it reached 91%.